PENGARUH PELATIHAN DAN PENGALAMAN KERJA TERHADAP PENGEMBANGAN KARIR KARYAWAN PERUMDA BPR KUNINGAN - Mei Saputra, Muhammad Rezal; Abdullah, Dudung; Hernita, Nita (Komunitas Manajemen Kompetitif, 2025)
A business's workforce, including its human resources and staff, represents the most valuable resource for reaching common objectives. The swift advancement of a business relies on its personnel.Therefore, if a company desires positive change andprogress in achieving its goals, the employees it employs must also possess strong skills. Therefore, the research aims to explain the influence of training and experience on the career development of Perumda BPR Kuningan employees.A survey using a descriptive and verification methodology was the research method employed. 113 Perumda BPR Kuningan employees made up the study's population. Using a straightforward saturation sampling technique and nonprobability sampling, the sample was chosen. A Likert scale was employed as the measurement tool in this investigation. Coefficient of determination analysis and multiple linear regression were employed in the data analysis. The classical assumption test was first performed, followed by a hypothesis test.According to the study's findings, career development is positively and significantly impacted by the training variable, at least in part. Career growth is positively and significantly impacted by the work experience variable, in part.